2019
DOI: 10.3892/ol.2019.11135
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑769‑3p inhibits tumor progression in glioma by suppressing ZEB2 and inhibiting the Wnt/β‑catenin signaling pathway

Abstract: Accumulating evidence suggests the crucial role of microRNAs (miRNAs) in human cancers. The present study aimed to investigate the clinical and functional roles of miR-769-3p in glioma, as well as the underlying molecular mechanisms. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to determine the expression levels of miR-769-3p in glioma tissues and cells. Receiver operating characteristic (ROC) curve analysis was applied to calculate the diagnostic value of miR-769-3p. The 5-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The 11 studies selected for the purpose of this study 20 21 22 23 24 25 26 27 28 29 30 as seen in Table 3 underwent random effect model for the overall survival analysis. This was due to significant heterogeneity being observed in the selected studies ( p < 0.05, I 2 = 85.9%).…”
Section: Resultsmentioning
confidence: 99%
“…The 11 studies selected for the purpose of this study 20 21 22 23 24 25 26 27 28 29 30 as seen in Table 3 underwent random effect model for the overall survival analysis. This was due to significant heterogeneity being observed in the selected studies ( p < 0.05, I 2 = 85.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Wang et al discovered that miR-769-3p blocked the Wnt/β-catenin pathway via targeting ZEB2 in glioma cells, thereby repressing tumor growth. 27 However, Ju et al revealed that miR-769-3p was a potential predictor of lung metastasis, which might be related to the specificity of cells and tissues. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Our data further elucidated the effects of ADAMTS9-AS1 on the molecular mechanisms underlying ADAMTS9-AS1 knockdown suppressing glioma cell proliferation, migration and invasion. Typically, activation of the Wnt/β-catenin signaling pathway is considered to be one of the most important molecular pathways involved in the development of various human cancers, including glioma (27,28). Moreover, inhibition of Wnt/β-catenin signaling can block the process of epithelial-mesenchymal transition (EMT) during the cancer progression (29).…”
Section: Discussionmentioning
confidence: 99%